Strontium-doped chromium oxide for RhB reduction and antibacterial activity with evidence of molecular docking analysis - Ikram, Muhammad; Shahzadi, Anum; Bilal, Muhammad; Haider, Ali; Ul-Hamid, Anwar; Nabgan, Walid; Haider, Junaid; Ali, Salamat; Medina, Francisco; Imran, Muhammad (Frontiers in Chemistry, 2023)
The emergence of multi-drug resistance (MDR) in aquatic pathogens and the presence of cationic dyes are the leading causes of water contamination on a global scale. In this context, nanotechnology holds immense promise for utilizing various nanomaterials with catalytic and antibacterial properties. This study aimed to evaluate the catalytic and bactericidal potential of undoped and Sr-doped Cr2O3 nanostructures (NSs) synthesized through the co-precipitation method. In addition, the morphological, optical, and structural properties of the resultant NSs were also examined. The optical bandgap energy of Cr2O3 has been substantially reduced by Sr doping, as confirmed through extracted values from absorption spectra recorded by UV-Vis studies. The field-emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM) micrographs illustrate that the composition of Cr2O3 primarily consisted of agglomerated, irregularly shaped NSs with a morphology resembling nanoflakes. Moreover, the presence of Sr in the lattice of Cr2O3 increased the roughness of the resulting NSs. The catalytic activity of synthesized NSs was analyzed by their reduction ability of Rhodamine B (RhB) dye in the dark under different pH conditions. Their antibacterial activity was evaluated against MDR Escherichia coli (E. coli). Sr doping increased antibacterial efficiency against MDR E. coli, as indicated by inhibition zone measurements of 10.15 and 11.75 mm at low and high doses, respectively. Furthermore, a molecular docking analysis was conducted to determine the binding interaction pattern between NSs and active sites in the target cell protein. The findings corroborated antimicrobial test results indicating that Sr-Cr2O3 is the most effective inhibitor of FabH and DHFR enzymes.